Edtech as fetish: Limits of school transformation processes - Pereira, Talita Vidal; Ferreira, Lhays Marinho (Education Policy Analysis Archives, 2018)
As an answer to the call from the Edtech and Policies of Human Formation dossier, the current article presents reflections resulting from the development of Master Degree research. Moreover, it has the aim of analyzing the senses given to the use of mobile devices by teacher’s professors in the classroom. It is an ethnographic study conducted in a teacher’s formation institution focused on the Normal High School Teaching. The institution is located in Rio de Janeiro City neighborhood. The study was performed based on the appropriation of post-structural and post-colonial inputs, and it addresses a concept of culture focused on the endless process of formulating meanings in order to analyze the cultural tensions deriving from the use of mobile devices during schooling processes, which are often underlined by a normativity frame motivated by teachers’ expectations about controlling the processes of signification. The text highlights arguments to support the understanding that the interactive and enhancing potential of mobile devices tends to be minimized within a context where school practices are supported by a schooling project marked by normative expectations and cultural standardization.